Hotel Accounting Including Departmental Control, Food Costing and Auditing (Book). - Benington, Harold (The Accounting Review, 1928)
Reviews the book "Hotel Accounting Including Departmental Control, Food Costing and Auditing," by Ernest B. Horwath and Louis Toth.